THE EFFECT OF THICKNESS AND DENSITY OF THE RECYCLED CAR TIRE PANELS ON SOUND INSULATION - Anđelko Crnoja; Željko Kos; Evgeny Klymenko; Iryna Grynyova (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta, 2021)
The article is devoted to the task of improving sound insulation in the construction of internal walls. For the experiment purposes wall panels were used that are made using rubber crumb as a separate structural layer. The analysis of the influence of the frequency range on the value of the sound insulation index was carried out. The effect of the particle size distribution of the mixture and the thickness of the wall panel on its soundproofing characteristics was investigated. Based on the results obtained, a conclusion was drawn about the influence of specific gravity on the sound insulation index.